Increase Students’ Motivation in Learning Science by Developing Instructional Media in The Form of Powtoon - Isnanik Juni Fitriyah*; Indra Fardhani (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Online learning that has been carried out more or less in the past year has caused student studying saturation. The provision of material through Youtube videos, articles or handouts in pdf form is generally done by teachers. In fact, technology has provided many alternatives that can be used as more interesting learning media, for example Powtoon. Therefore, this study aims to provide training to teachers in developing materials in the form of Powtoon in order to increase students' learning motivation, especially during online learning. This research includes community service research. The steps taken are; 1) Pre-implementation, in the form of needs analysis, 2) Implementation, in the form of training with Powtoon development materials as learning media, filling out questionnaires, independent work, discussions and 3) Post-implementation, in the form of evaluation of activities. The implementation of the training showed the enthusiasm of the participants as seen from the life of the discussion session. Based on the questionnaire filled out by the participants, the implementation of the training has been well implemented with suggestions for adding other innovative media materials, and improving teacher competence in other matters. In addition, the results of the development and use of Powtoon media carried out by participants showed that students were enthusiastic and motivated in learning